Green infrastructure impacts in winegrowing: A systematic map - Ebba Engström; Robert Fish; Caroline Howe; Catherine Matilda Collins; Benjamin J. Roberts; Samuel Watkins; Alexandra Collins (Agriculture, Ecosystems & Environment, 2025)

Managing offshore multi-use settings: Use of conceptual mapping to reduce uncertainty of co-locating seaweed aquaculture and wind farms - Ryan O'Shea; Elisa Capuzzo; Victoria Hemming; Gretchen Grebe; Rick Stafford; Sander W.K. van den Burg; Daniel Wood; Gordon Watson; Victoria Wells; Teresa Johnson; Stefan Erbs; Jaap W. van Hal; et al. (Journal of Environmental Management, 2024)

Contrasting relationships between socio-economic status and avian ecosystem service provision in a developing world city - Chevonne Reynolds; Caroline G. Howes (Landscape and Urban Planning, 2023)

A trait-based assessment of southern African arid-zone birds' vulnerability to climate change - Stephanie L. Payne; Susan J. Cunningham; Caroline G. Howes; Andrew E. McKechnie (Biological Conservation, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Highly skewed sex and age ratios of European Honey Buzzard in southern Africa - Caroline Howes; Craig T. Symes; Patrik Byholm (Journal of Ornithology, 2020)

Risk of genetic maladaptation due to climate change in three major European tree species - Aline Frank; Glenn T. Howe; Christoph Sperisen; Peter Brang; J. Bradley St. Clair; Dirk R. Schmatz; Caroline Heiri (Global Change Biology, 2017)
Tree populations usually show adaptations to their local environments as a result of natural selection. As climates change, populations can become locally maladapted and decline in fitness. Evaluating the expected degree of genetic maladaptation due to climate change will allow forest managers to assess forest vulnerability, and develop strategies to preserve forest health and productivity. We studied potential genetic maladaptation to future climates in three major European tree species, Norway spruce ( Picea abies ), silver fir ( Abies alba ), and European beech ( Fagus sylvatica ). A common garden experiment was conducted to evaluate the quantitative genetic variation in growth and phenology of seedlings from 77 to 92 native populations of each species from across Switzerland. We used multivariate genecological models to associate population variation with past seed source climates, and to estimate relative risk of maladaptation to current and future climates based on key phenotypic traits and three regional climate projections within the A1B scenario. Current risks from climate change were similar to average risks from current seed transfer practices. For all three climate models, future risks increased in spruce and beech until the end of the century, but remained low in fir. Largest average risks associated with climate projections for the period 2061–2090 were found for spruce seedling height (0.64), and for beech bud break and leaf senescence (0.52 and 0.46). Future risks for spruce were high across Switzerland. However, areas of high risk were also found in drought‐prone regions for beech and in the southern Alps for fir. Genetic maladaptation to future climates is likely to become a problem for spruce and beech by the end of this century, but probably not for fir. Consequently, forest management strategies should be adjusted in the study area for spruce and beech to maintain productive and healthy forests in the future.

Distinct genecological patterns in seedlings of N orway spruce and silver fir from a mountainous landscape - Aline Frank; Christoph Sperisen; Glenn Thomas Howe; Peter Brang; Lorenz Walthert; John Bradley St.Clair; Caroline Heiri (Ecology, 2017)
Understanding the genecology of forest trees is critical for gene conservation, for predicting the effects of climate change and climate change adaptation, and for successful reforestation. Although common genecological patterns have emerged, species‐specific details are also important. Which species are most vulnerable to climate change? Which are the most important adaptive traits and environmental drivers of natural selection? Even though species have been classified as adaptive specialists vs. adaptive generalists, large‐scale studies comparing different species in the same experiment are rare. We studied the genecology of Norway spruce ( Picea abies ) and silver fir ( Abies alba ), two co‐occurring but ecologically distinct European conifers in Central Europe. For each species, we collected seed from more than 90 populations across Switzerland, established a seedling common‐garden test, and developed genecological models that associate population variation in seedling growth and phenology to climate, soil properties, and site water balance. Population differentiation and associations between seedling traits and environmental variables were much stronger for Norway spruce than for silver fir, and stronger for seedling height growth than for bud phenology. In Norway spruce, height growth and second flushing were strongly associated with temperature and elevation, with seedlings from the lowlands being taller and more prone to second flush than seedlings from the Alps. In silver fir, height growth was more weakly associated with temperature and elevation, but also associated with water availability. Soil characteristics explained little population variation in both species. We conclude that Norway spruce has become an adaptive specialist because trade‐offs between rapid juvenile growth and frost avoidance have subjected it to strong diversifying natural selection based on temperature. In contrast, because silver fir has a more conservative growth habit, it has evolved to become an adaptive generalist. This study demonstrates that co‐occurring tree species can develop very different adaptive strategies under identical environmental conditions, and suggests that Norway spruce might be more vulnerable to future maladaptation due to rapid climate change than silver fir.

A comparative approach to assess drivers of success in mammalian conservation recovery programs - Jennifer J. Crees; Amy C. Collins; P. J. Stephenson; Helen M. R. Meredith; Richard P. Young; Caroline Howe; Mark R. Stanley Price; Samuel T. Turvey (Conservation Biology, 2016)
The outcomes of species recovery programs have been mixed; high‐profile population recoveries contrast with species‐level extinctions. Each conservation intervention has its own challenges, but to inform more effective management it is imperative to assess whether correlates of wider recovery program success or failure can be identified. To contribute to evidence‐based improvement of future conservation strategies, we conducted a global quantitative analysis of 48 mammalian recovery programs. We reviewed available scientific literature and conducted semistructured interviews with conservation professionals involved in different recovery programs to investigate ecological, management, and political factors associated with population recoveries or declines. Identifying and removing threats was significantly associated with increasing population trend and decreasing conservation dependence, emphasizing that populations are likely to continue to be compromised in the absence of effective threat mitigation and supporting the need for threat monitoring and adaptive management in response to new and potential threats. Lack of habitat and small population size were cited as limiting factors in 56% and 42% of recovery programs, respectively, and both were statistically associated with increased longer term dependence on conservation intervention, demonstrating the importance of increasing population numbers quickly and restoring and protecting habitat. Poor stakeholder coordination and management were also regularly cited by respondents as key weaknesses in recovery programs, indicating the importance of effective leadership and shared goals and management plans. Project outcomes were not influenced by biological or ecological variables such as body mass or habitat, which suggests that these insights into correlates of conservation success and failure are likely to be generalizable across mammals.

Leftward shift in the acquisition of cocaine self-administration in isolation-reared rats: relationship to extracellular levels of dopamine, serotonin and glutamate in the nucleus accumbens and amygdala-striatal FOS expression - Simon R. Howes; Jeffrey W. Dalley; Caroline H. Morrison; Trevor W. Robbins; Barry J. Everitt (Psychopharmacology, 2000)